Fenomena Njanthur Dalam Pertunjukan Kuda Lumping Paguyuban Seni Cahyo Kumolo Di Desa Ambalkumolo Kabupaten Kebumen - Salma Dinar Nugrahaeni; Eny Kusumastuti (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the phenomenon of njanthur   in the Kuda Lumping performance of Cahyo Kumolo Art Group in Ambalkumolo Village, Kebumen Regency. The research employed a qualitative method using a phenomenological approach and a case study design. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings indicate that njanthur   occurs through three stages: pre-performance, main performance, and post-performance. The pre-performance stage involves ritual preparations, including prayers, offerings, and incense burning. During the main performance, njanthur   emerges through a combination of dance movements, musical accompaniment, chants, whip use, and the janthuran mayit sequence, leading dancers into an altered state of consciousness. Two forms of njanthur   were identified, namely technical njanthur   (surupi) and non-technical njanthur   (possession trance). The post-performance stage focuses on restoring the dancers’ awareness through ritual healing practices. Interpreted through Charles Tart’s Altered State of Consciousness theory, njanthur   reflects a culturally embedded form of altered consciousness. The study highlights the central role of the penimbul in managing rituals, supervising dancers, and facilitating the recovery process throughout the performance.